The Effect of HRM Pratices on Employee Engagement with Clan Culture as Moderating Variables - Inatun Yustrilia; Anton Sujarwo; Ainur Rofiq; Dwi Ratmawati; Bagus Satriyo (Universitas muhammadiyah malang, 2022)
To maintain and improve competitiveness, exploring potentials and innovations to survive in the competition aimed at attracting student interest and gaining public recognition at the national and global levels (World Class University), universities must improve employee engagement. Because high employee engagement is a source of organizational competitive advantage in achieving its vision, mission, main goals and implementing organizational strategies at the global level. To improve employee engagement with improving HRM Practices. In this study, testing the effect of HRM practices on employee engagement with clan culture as a moderating variable. The results of these tests are expected to be a reference for organizations to improve employee engagement. Questionnaires were distributedto 154 employees of universities in Surabaya with varying criteria. After the questionnaires were collected, statistical tests were performed using Partial Least Square (PLS). The results of statistical testing found that employee engagement are influenced by training & development, performance appraisal and compensation. Meanwhile, clan culture only moderates the relation between compensation for employee engagement, and does not moderate the relations between training & development and performance appraisal on employee engagement. Results of this study may be employed as a policy consideration and further contribute to the literature of management studies.